LIQUIDITY MANAGEMENT AND FINANCIAL PERFORMANCE OF LISTED OIL AND GAS COMPANIES IN NIGERIA - Alhassan, Ismail; Islam, K. M. Anwarul (International Journal of Accounting & Finance Review, 2021)
The purpose of this paper is to figure out the link between liquidity and profitability, as well as the impact of liquidity on profitability. Ten listed companies with a bigger market share in the oil and gas sector of the Nigerian economy were subjected to a fixed panel regression study. Secondary data was gathered for ten years, from 2011 to 2020, from their published annual reports. Profit after tax (PAT), Return on Asset (ROA), and Return on Equity (ROE) were used to determine profitability (ROE). Internal liquidity variables such as equity, debt, and sales were utilized to determine the behavior of the dependent variable, but external elements such as lending interest rate and exchange rate were employed to further explain profitability behavior. The data were analyzed using a multiple regression approach. The findings reveal that debt has a significant negative impact on companies' profitability. Similarly, equity capital, as well as retained earnings, are more beneficial to firms than the debt financing of the oil and gas sector. The study, therefore, recommends that oil and gas firms should boost their equity capital, improve their revenues, increase their retain earnings, and reduce debt financing to enable them to generate more wealth for shareholders. JEL Classification Codes: F65.